The local finance reforme and the promotion of the economic role of the municipality - Doubabi, Nadira; Brahmi, Boutaleb (Journal of Human Sciences, 2022)
The present study proposes recommendations related to the local authorities’ finance reforme and the local funding, through the budget mastery mechanisms (enhancing of local financial resources and expenditure control) and also the promotion of the municipality’s economic role through the involvement of the "territory" in a real dynamic of investment aimed at enhancing local potential and supporting SMEs in the wealth increasing. The study emphasizes also on the need to adopt public- private partnership as an effective model for financing local development.